Impact of Training on Knowledge, Attitude and Perceived Barriers for Compliance Regarding use of Personal Protective Equipment Kit among Frontline Healthcare Workers during COVID-19 Pandemic - Jyoti Sangwan; Sumit Lathwal; Kirti Lohan; Kumkum Yadav; Neha Adlakha; Pratibha Mane; Sheetal Gole (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), the novel Coronavirus, the causative agent of Coronavirus Disease-2019 (COVID-19) pandemic has grasped the whole world. Healthcare Workers (HCWs) are at an increased risk. The usage and awareness of entire Personal Protective Equipment (PPE) kit in hospitals on such wide scale has not been seen for some time in healthcare setting. Improper use of these equipment may result in the spread of infection. Aim: To assess the knowledge and attitude of HCWs regarding the correct use of PPE at the beginning of COVID-19 pandemic in order to find the gap in knowledge and to address the perceived barriers in compliance and further to assess the same after training and reinforcement to ensure the HCWs safety. Materials and Methods: A cross-sectional hospital based study was carried out in a designated COVID-19 hospital of Shaheed Hasan Khan Mewati Government Medical College from April 2020 to October 2020 on frontline HCWs posted in various areas of hospital. Sample size was calculated as a minimum of 500 HCWs using appropriate statistical formula. A predesigned, pretested structured questionnaire both online and offline mode was used. The data that was obtained was analysed using Statistical Package for the Social Science (SPSS) version 20.0. Results: Seven hundred frontline HCWs were included in the study. Mean age of study population was 30.5 years. Among 700 HCWs, 200 (28.57%) were doctors, 360 (51.42%) were nursing staff and 140 (20%) were housekeeping staff. Knowledge level of PPE kit and its use varied across doctors, nursing staff and housekeeping staff. Knowledge about donning and doffing was largely lacking with only 9% doctors and none of other staff were aware which improved to more than 80% post-training. Attitude regarding PPE kit usage was largely positive. Conclusion: The study concludes that there is a constant need of training and re-training of HCWs in order to keep them safe from not only COVID-19 but also from future infections. An active infection prevention training program is crucial to ensure HCWs safety.